Dampak Bullying Terhadap Kesehatan Psikologis Mahasiswa - Aravia Balqis; Natasya Putri Riza Aulia; Fatma Tresno Ingtyas; Laurena Ginting (Badan Penerbit STIEPARI Press, 2026)
Bullying in higher education environments is a phenomenon that often escapes attention, yet it has numerous significant impacts on students’ psychological well-being. This study aims to examine the effects of bullying that occur within the student community, particularly its mental health and psychological consequences. Bullying is typically perpetrated by individuals who perceive themselves as stronger toward those they consider weaker. This research employs a qualitative phenomenological design using in-depth interview methods. The participants are students who have experienced bullying, selected through purposive sampling. Data were collected through interviews and field notes, analyzed using the Colaizzi technique. The findings reveal that participants experienced various forms of bullying, including psychological and social abuse. The impacts reported by participants include stress, anxiety disorders, depression, decreased academic performance, and social isolation. These findings emphasize the crucial role of institutions in fostering a safe, supportive, and psychologically violence-free campus environment. Comprehensive prevention and intervention policies are required to protect students’ psychological health and ensure optimal academic progress.